Opening spaces for researching feminism and public relations: Perspectives from Australia, Indonesia and Malaysia. (January 2023) - Fitch, Kate; Clark, Treena; Kaur, Kiranjit; Simorangkir, Deborah N.; Souket, Rizwanah
Drawing on communication, feminist studies and public relations scholarship, this interdisciplinary paper contributes to feminist perspectives on public relations in order to draw attention to the disciplinary implications of the ongoing exclusion of diverse women's voices and the ways gendered exclusion is exacerbated by the marginalisation of voices from Global South, Indigenous and settler colonial contexts. Writing from three countries located in the Asia-Pacific region, the authors interrogate the field as feminist public relations scholars and highlight the need for more inclusive practices in academic processes that shape disciplinary knowledge. The paper challenges liberal feminist and postfeminist perspectives, arguing these have significant implications for the production of public relations knowledge. Instead, it argues that feminist public relations scholarship needs to foreground intersectionality and social justice and embrace perspectives and research outside the US and Europe. It calls for greater awareness of the ways power is associated with privilege and determines 'legitimate' disciplinary knowledge within public relations in order to challenge structural and institutional inequalities. In advocating for critical, intersectional and transnational feminist public relations, the paper argues for greater reflexivity and vigilance in opening up the field to new and diverse perspectives and improving disciplinary processes.